2021
DOI: 10.23938/assn.0955
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of in hospital nonagenarians with acute kidney injury

Abstract: Fundamento. El desarrollo de un fracaso renal agudo (FRA, definido siguiendo las guías KDIGO) durante una hospitalización en pacientes nonagenarios ha sido poco estudiado. El objetivo del presente estudio es analizar la mortalidad en pacientes nonagenarios hospitalizados que desarrollan un FRA.Métodos. Se recogieron todos los pacientes nonagenarios que desarrollaron FRA durante el ingreso hospitalario entre 2013 y 2014. Basalmente, se recogieron variables epidemiológicas, comorbilidades y, durante el ingreso, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In-hospital mortality in nonagenarians with AKI according to published articles ranges from 23% to 70%, depending on mean age, patient severity, comorbidity profile and criteria for defining AKI 3 , 4 , 6 . In our study, we observed a mortality rate of 56.7%, similar to other published data, which may be justified by the prevalence of comorbidities and severity of the study group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In-hospital mortality in nonagenarians with AKI according to published articles ranges from 23% to 70%, depending on mean age, patient severity, comorbidity profile and criteria for defining AKI 3 , 4 , 6 . In our study, we observed a mortality rate of 56.7%, similar to other published data, which may be justified by the prevalence of comorbidities and severity of the study group.…”
Section: Discussionmentioning
confidence: 99%
“…In the surviving group, there was a high prevalence of CKD, KDIGO 1 and dehydration/hypovolemia. Data suggest that CKD patients who develop AKI have a lower risk of death 17 , and are not associated with worse outcomes 3 . In our study, although CKD was more prevalent in the survivor group (50.8%, p = 0.019), it was not identified as a lower risk factor for mortality in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations